Association of alternative healthy eating index and severity of pemphigus vulgaris: A cross-sectional study - Fallah, Maryam; Najafi, Anahita; Balighi, Kamran; Daneshpazhooh, Maryam; Ebrahimpour-Koujan, Soraiya (PloS one, 2023)
Evidence on the association between following healthy eating and the severity of pemphigus vulgaris (PV) is scarce. Therefore, the aim of this cross-sectional study aimed to investigate the relationship between adherence to the alternative healthy eating index (AHEI) and the severity of Pemphigus vulgaris disease in adults. In this hospital-based cross-sectional study, a total of 138 pemphigus vulgaris cases were studied, of which 108 had pemphigus disease area index (PDAI) ≤15, and 30 had PDAI>15. Dietary intakes were assessed using a valid 168-item food frequency questionnaire (FFQ). To calculate the AHEI, the data received from the diet were used. The subjects of this index received a score of 1-10. The final AHEI was calculated by summing the component scores. After adjusting for age and sex, we found that individuals with the highest AHEI score were 72% less likely to have increased PV severity compared with those with the lowest score (OR: 0.28; 95% CI: 0.08-0.92, P trend = 0.020). Further control for another potential confounder, intake energy, made the association stronger (OR: 0.24; 95% CI: 0.06-0.88, P trend = 0.017). Also, after controlling the body mass index (BMI) confounding factor, it maintained its strong relationship (OR: 0.24; 95% CI: 0.06-0.88, P trend = 0.016). The evidence of our study shows that following the healthy eating index is associated with a reduction in the severity of pemphigus vulgaris. Prospective cohort studies are needed to confirm these findings.